HEGEMONI AMERIKA SERIKAT DI ASIA TENGGARA - Salman Al Paris Sormin Salman Al Paris Sormin (Institut Pendidikan Tapanuli Selatan, 2018)
The arrival of the United States was first to Southeast Asia more driven by economic interests. However, after the end of World War II political and security interests became a major consideration for the country. As a new imperial power in the world, the presence of the United States in Southeast Asia has had a major impact on the region, both politically, economically, and in terms of security. Even that influence continues to this day. The involvement of the United States in the arena of politics and security in Southeast Asia, especially since the end of World War I, I was not a groundless act. Although the territory of the United States is not so wide in Southeast Asia, it only covers the Philippines, but the political implications are very great for countries in Southeast Asia. The importance of Southeast Asia for the United States can be seen from sharing aspects, namely: Geo Economical, Geo Strategic, Geo Politis. Geo Economically Southeast Asia is important for America as an export and import partner.